Pre-Service Elementary Teachers’ Perceptions of Advanced Basic Science Courses in Supporting Teaching Competencies - Nofamataro Zebua; Ester Novi Kurnia Zebua; Muhammad Andi Tanri Prasetyo; Sherly Hariyanti (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2026)
The low level of scientific reasoning skills and conceptual understanding among pre-service elementary school teachers remains a significant challenge in science education at the higher education level. This condition reflects a gap between students’ mastery of scientific theories and their ability to connect scientific concepts with instructional practices in primary education. This study aims to examine the perceptions of pre-service primary school teachers toward the Advanced Fundamental Science Concepts course in supporting their professional teaching competencies. The study employed a descriptive quantitative approach supported by qualitative data obtained through interviews. Data were collected using a questionnaire consisting of 20 validated and reliable statements, which was voluntarily administered to 36 students enrolled in the Primary Teacher Education Program. Data analysis was conducted using descriptive statistics in the form of percentages, while interview data were analyzed qualitatively to strengthen and enrich the research findings. The results indicate that students demonstrated positive perceptions toward the Advanced Fundamental Science Concepts course, particularly in terms of understanding fundamental science concepts (84%) and the relevance and application of science concepts (81%). The findings further reveal that students have recognized science as a scientific reasoning process; however, they continue to encounter difficulties in data analysis and scientific inference skills. Therefore, science education in teacher preparation programs should place greater emphasis on strengthening scientific reasoning competencies through inquiry-based and practice-oriented learning approaches.